O saneamento básico e a internet das coisas: os díspares avanços na cidade de São Paulo - Custódio, Gustavo Correia de Aquino (2022)
With the population growth of urban regions, several interventions must be taken in the infrastructure of cities, such as the creation of complex systems for the treatment and transport of water, and for the collection and adequacy of sanitary evictions to be properly sent to nature. The diverse Brazilian reality is also present in this field, presenting very different panoramas between the regions, both in the offering of treated water, as well as in the correct handling of the collected sewage. Despite numerous advances in this area in recent decades, indicators of the coverage of sanitation networks are still far from providing the necessary security, aggravated in needy populations, and swelled in complex social-economic problems. Different plans for the expansion of urban sanitation were elaborated by different Brazilian governments and at different periods of history. In this context, legislation and regulatory frameworks were created, regulating departments and secretariats at all levels of government in the continuous work for the universalization of access to basic sanitation of the population. At the same time, the evolution of sensing, highprocessing and data transmission technologies developed in recent decades bring to the scene new paradigms that will help in the provision of quality sanitation services to the population, besides involving citizens directly as participating agents and supervisors of natural resources, dependent and belonging to all